Acute stress-induced cortisol elevation during memory consolidation enhances pattern separation - Jiang, Alice; Tran, Tammy T.; Madison, Farrah N.; Bakker, Arnold (Learning & memory (Cold Spring Harbor, N.Y.), 2019)
Stress is a potent modulator of brain function and particularly mnemonic processes. While chronic stress is associated with long-term deficits in memory, the effects of acute stress on mnemonic functions are less clear as previous reports have been inconsistent. Some studies suggest that cortisol, a stress hormone that modulates biological changes in response to stress, may enhance memory consolidation and impair memory retrieval. However, other studies report no effect of cortisol on either memory consolidation or retrieval. These discrepancies could be due to differences in the timing and sequencing of the experimental procedures or individual differences in participants’ stress response. In the present study, we examined the effect of increased cortisol levels due to acute stress, induced by the Trier Social Stress Test (TSST), on a pattern separation memory task while differentiating the distinct stages of memory processing and controlling for the effects of diurnal variation. Sixty-nine young adults completed a 2-d study in which subjects either underwent the TSST immediately following the encoding part of the memory task, targeting memory consolidation, or immediately prior to the recognition part of the memory task on the second day, targeting memory retrieval. Control subjects completed the same study procedures but underwent a control version of the TSST that did not induce a stress response. Mnemonic discrimination of highly similar stimuli was enhanced by stress induced during consolidation with better discrimination showing a significant correlation with increased cortisol responses. Stress induced during memory retrieval showed no significant effect on memory performance. These findings suggest that stress induced changes in cortisol differentially affect the consolidation and retrieval stages of memory function.